What Digital Divide between Generations? A Cross-National Analysis Using Data from the World Internet Project - Lapa, T.; Cardoso, G. (7th International Conference, UAHCI 2013, Held as Part of HCI International, 2013)
Individuals who grew up in the digital age are, according to some, digital natives, with increased expertise, compared to the rest of the population, using digital technology as an integral part of their lives. However, this paper aims to make a critical evaluation of approaches that naturalize the notion of "digital native," supported by the available data of the World Internet Project (WIP 2010) regarding the relationship of individuals of different cohorts with new technologies. Using the concept of digital natives without carrying out a careful and extensive comparative analysis runs the risk of masking asymmetric social situations (social, economic, geographic, gender, educational, cultural), both in younger and in older adults. Our proposed analysis takes into account alternative proposals that argue that the extent of use and experience has greater explanatory power than the simple comparison of inter-generational use of new technologies.